2017
DOI: 10.1186/s12991-017-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between an angiotensin-converting enzyme gene polymorphism and Alzheimer’s disease in a Tunisian population

Abstract: Background:The angiotensin-converting enzyme gene (ACE) insertion/deletion (I/D or indel) polymorphism has long been linked to Alzheimer's disease (AD), but the interpretation of established data remains controversial. The aim of this study was to determine whether the angiotensin-converting enzyme is associated with the risk of Alzheimer's disease in Tunisian patients. Methods:We analyzed the genotype and allele frequency distribution of the ACE I/D gene polymorphism in 60 Tunisian AD patients and 120 healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…A study in southeast Turkey indicated that women with DD or ID genotypes had a 72% increased risk of idiopathic recurrent pregnancy loss [12], while another study in northern Iran found the DD genotype to be more prevalent among women who have experienced recurrent pregnancy loss [13]. Additionally, the I/D polymorphism has been found to be associated with Alzheimer's disease; however, both the I allele [14,15] and the D allele [16] have been found to be associated with an increased risk of developing the disease. Other studies have found the I/D polymorphism to be associated with various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…A study in southeast Turkey indicated that women with DD or ID genotypes had a 72% increased risk of idiopathic recurrent pregnancy loss [12], while another study in northern Iran found the DD genotype to be more prevalent among women who have experienced recurrent pregnancy loss [13]. Additionally, the I/D polymorphism has been found to be associated with Alzheimer's disease; however, both the I allele [14,15] and the D allele [16] have been found to be associated with an increased risk of developing the disease. Other studies have found the I/D polymorphism to be associated with various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…-Higher cortisol levels can enhance tau hyperphosphorylation, apoptosis, synaptic loss and mitochondrial dysfunction [70]. Delayed autoimmune response -SARS-CoV-2 may remain latent in neurons [11] meningoencephalitis, viral RNA was not detectable, which may be suggestive of transient or undetectable amounts of viral RNA in CNS [90,91].…”
Section: Cytokine Storm: Neuroimmune Mechanismsmentioning
confidence: 99%
“…This indicates that ACE-2 downregulation, induced by SARS-CoV-2 infection, might be associated with concomitant alterations in dopamine synthetic pathway, which is implicated in pathophysiology of PD [122]. Furthermore, ACE-2 gene polymorphisms have been shown to influence susceptibility to infection with COVID-19 and its complications such as multi-organ failure, although the exact association has not been determined [123,124], while specific ACE-2 polymorphisms can potentially increase the risk for PD [125] and AD [70].…”
Section: Angiotensin-converting Enzymes: Neuroprotective and Neurotoxmentioning
confidence: 99%
“…The D allele was also more frequently found in patients compared with controls (71.67 vs. 56.25%; p = 0.003, OR = 2.0). Moreover, as assessed by Mini-Mental State Examination, patients suffering from severe dementia were found predominantly in the D/D carriers group and, conversely, the D/D genotype and D allele were more frequently found in AD patients with severe dementia ( 130 ).…”
Section: Ace2 Neurological Functioning and Disease: Clinical Evidencmentioning
confidence: 96%